Goal-framing theory: uma análise das dos objetivos de ganho, hedônico e normativo e suas relações com a decisão de compra do consumidor - Costa, Thiago Chiorino (2020)
This study proposes to advance the theoretical knowledge about the Goal Framing Theory. In addition to explaining and organizing the theoretical framework on the framing effect, the Consumer Motivation Scale was adapted and validated through Exploratory and Confirmatory Factor Analysis. As a result, the scale proved to be consistent with the Goal Framing Theory, and its gain, hedonic and normative goal, in seven dimensions. In addition, in a survey carried out with 448 individuals, a simulation of the purchase choice of two products, t-shirt and ketchup, to assess the relationship between the seven dimensions of the scale with the brand, price and organic attributes of the products. The regression analyzes performed showed a positive relationship between the gain goal and the price attribute, while the hedonic goal showed a relationship with organic product. A series of other theoretical discussions and managerial implications are discussed at the end of the work. The work fulfills the objective of confirming existing assumptions in the theory, and consolidates the Goal Framing Theory as another explanatory theory of the motivations that lead individuals to make decisions.